Reproductive Anxiety and Conditional Agency at the Intersections of Privilege: A Focus Group Study of Emerging Adults' Perception of Long‐Acting Reversible Contraception. (22nd December 2019) - Grzanka, Patrick R.; Schuch, Elena
Abstract: Public health officials and major health care organizations in the United States have identified long‐acting reversible contraception (LARC) as the first‐line option for preventing unintended pregnancy. Existing research on LARC focuses on efficacy and usage rates, generally effacing women's lived experiences with these historically controversial devices. We take a critical, reproductive justice‐informed approach to LARC promotion efforts in this qualitative, focus group study. Across six groups of undergraduate women ages 18–24 ( N = 30, majority White), we explore how the individuals targeted by contemporary LARC promotion efforts—emerging adult women who have never given birth—negotiate (not) acquiring these devices. We introduce reproductive anxiety and conditional agency as key terms through which our participants made meaning out of LARC. Though participants reflected socially normative discourses of empowerment and choice, our findings suggest that these relatively privileged respondents experienced their choices to use or not use LARC in neoliberal terms. Specifically, we suggest their responses avert attention from the multifarious ways that women's reproductive capacities are differentially disciplined by hegemonic norms. We conclude by suggesting that sexual and reproductive health policy must foreground issues of structural intersectionality—rather than cost or efficacy—so that health promotion efforts do not inadvertently exacerbate inequalities.